Pelagic occurrences of the ice amphipod Apherusa glacialis throughout the Arctic. (10th January 2020) - Kunisch, Erin H; Bluhm, Bodil A; Daase, Malin; Gradinger, Rolf; Hop, Haakon; Melnikov, Igor A; Varpe, Øystein; Berge, Jørgen
Abstract: Apherusa glacialis is a common, sea ice-associated amphipod found throughout the Arctic Ocean and has long been considered permanently associated with the sea ice habitat. However, pelagic occurrences of A. glacialis have also been reported. It was recently suggested that A. glacialis overwinters at depth within the Atlantic-water inflow near Svalbard, to avoid being exported out of the Arctic Ocean through the Fram Strait. This study collated pelagic occurrence records over a 71-year period and found that A. glacialis was consistently found away from its presumed sea ice habitat on a pan-Arctic scale, in different depths and water masses. In the Svalbard region, A. glacialis was found in Atlantic Water both in winter and summer. Additionally, we analyzed A. glacialis size distributions throughout the year, collected mostly from sea ice, in order to elucidate potential life cycle strategies. The majority of young-of-the-year A. glacialis was found in the sea ice habitat during spring, supporting previous findings. Data on size distributions and sex ratios suggest a semelparous lifestyle. A synchronous seasonal vertical migration was not evident, but our data imply a more complex life history than previously assumed. We provide evidence that A. glacialis can no longer be regarded as an autochthonous sympagic species.